2008
DOI: 10.1007/s10286-008-0473-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovarian hormones and aging on respiratory sinus arrhythmia and breathing patterns in women

Abstract: We investigated the effect of ovarian hormones and aging on breathing pattern [pulmonary minute ventilation (V(E))], tidal volume (V(T)), breathing frequency (F(b)), and respiratory sinus arrhythmia (RSA) in women. Recordings of V(E) and electrocardiogram (ECG) were obtained from 23 healthy women (10 premenopausal, 13 postmenopausal) under resting, isocapnic hypoxia (IH), and euoxic hypercapnia (EH) conditions. Premenopausal women were tested on three different days, each day corresponding to a specific phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A total of 45 studies published between the year 1995 and October 2018 were included in the systematic review [40,42,43,44,45,49,50,51,52,53,54,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90]. Only one of the 45 studies was published in Russian [43]; all others were written in English.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 45 studies published between the year 1995 and October 2018 were included in the systematic review [40,42,43,44,45,49,50,51,52,53,54,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90]. Only one of the 45 studies was published in Russian [43]; all others were written in English.…”
Section: Resultsmentioning
confidence: 99%
“…A total of seven publications ( n individuals = 107) did not report sufficient quantitative data in the manuscript and data could not be retrieved from the corresponding authors after four contact attempts [49,51,60,69,79,81,83]. These studies could not be included in the meta-analysis; however, their general results regarding the comparison between follicular and luteal cycle half are described here: One of the seven studies is consistent with the result of the meta-analysis, as they report a significant decrease in CVA from the follicular to the luteal phase [60].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies confirmed both the increase in baseline ventilation due to an effect on respiratory frequency [171] and hyperventilation and lower PaCO 2 during the luteal phase, when progesterone levels are higher than during the follicular phase [41, 172-174]. Similarly, breathing changes related to reduced synthesis of female sexual hormones during menopause confirmed their stimulatory effect, as ventilation is lower and PaCO 2 higher in postmenopausal than premenopausal women [36, 175]. In addition, administration of synthetic progestin to healthy men leads to increased ventilation and decreased PaCO 2 [34, 38, 176].…”
Section: Facilitation Of the Central Respira-tory Drive By Natural Prmentioning
confidence: 92%
“…Both responses could explain the higher VE observed during the MLP. The increase in VE and inspiratory flow may indicate the influence of progesterone in stimulating the respiratory drive, either centrally as explained above, or peripherally, or by both [ 37 ]. Another possible reason to explain the higher VT and BF during the MLP is the influence of ovarian hormones on the contractile component of respiratory muscles [ 38 ].…”
Section: Discussionmentioning
confidence: 99%